2010
DOI: 10.1116/1.3425640
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of aluminum-doped zinc oxide thin films for optical applications using rf and dc magnetron sputter deposition

Abstract: Aluminum-doped zinc oxide films were deposited by dc and rf magnetron sputtering from ZnO(98%)Al2O3(2%) target at room temperature on silicon and glass substrates under a variety of process conditions with the goal of attaining the highest transmittance and lowest resistivity for photovoltaic applications. The magnetron power and pressure were varied. For many dielectric deposition systems, added oxygen is necessary to achieve the appropriate stoichiometry. The effect of oxygen on film properties was then stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Average percentage transmission in the visible region of most of the films was in the range of 92-95%. Similar values of transmission in the visible region have been reported [36,37]. Transparency of the film in the visible region is not much effected with films deposited at the higher power and higher substrate temperature, whereas, the absorption of the film increases in the IR region with the increase in the deposition power and substrate heating temperature.…”
Section: Methodssupporting
confidence: 79%
“…Average percentage transmission in the visible region of most of the films was in the range of 92-95%. Similar values of transmission in the visible region have been reported [36,37]. Transparency of the film in the visible region is not much effected with films deposited at the higher power and higher substrate temperature, whereas, the absorption of the film increases in the IR region with the increase in the deposition power and substrate heating temperature.…”
Section: Methodssupporting
confidence: 79%
“…[5] In particular, there is ad istinct lack of printable electrode materials,w ith silver inks currently employed to create the cathode in the bulk of reported printed OPV structures.T hough this approachh as produced single modules with efficiencies exceeding3%a nd has allowed upscaled manufacture to installationsp roducing more than 10 kV by linking upwards of 100 000 cells with ef-ficiencies of 1.5 %i ns eries, [6] moving from thermally evaporated cathode deposition on the small scale to printed cathode depositiono nt he R2R scale remains as ignificant challenge. [7] Sputtering of metal contacts has provent ob easuccessful route for massp roduction of liquid-crystal displays, [8] and presentss ome uniquea dvantages compared to printable cathodes.T he technology is compatible with large-area substrates,c an deposit ar ange of materials including pure metals,a lloys,a nd oxide semiconductors, [9,10] and does not suffer wettabilityi ssues,r esulting in compatibilityw ith aw ide range of device architectures.F urthermore,s puttering…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the resistivity of GZO films deposited by ALD is sensitive to oxygen during post-annealing, as reported previously. 10 Although the resistivity of GZO deposited on glass increases over 1000 times after post-annealing in oxygen ambient, the crystallinity of GZO films do not show an obvious change observed from X-ray diffraction patterns. 8,[11][12][13] On the other hand, it is found that the resistivity of GZO film can be preserved by passivating the dielectric layer onto the GZO surface.…”
Section: Methodsmentioning
confidence: 94%